EHealth parent education for hearing aid management: a pilot randomized controlled trial. (23rd July 2021) - Muñoz, Karen; San Miguel, Guadalupe G.; Barrett, Tyson S.; Kasin, Courtney; Baughman, Kelsey; Reynolds, Bailey; Ritter, Caitlyn; Larsen, Makynzie; Whicker, John J.; Twohig, Michael P.
Abstract: Objective: Parents frequently experience challenges implementing daily routines important for consistent hearing aid management. Education that supports parents in learning new information and gaining confidence is essential for intervention success. We conducted a pilot study to test an eHealth program to determine if we could implement the program with adherence and affect important behavioural outcomes compared to treatment as usual. Design: Randomised controlled trial. Study sample: Parents of children birth to 42 months who use hearing aids. Eighty-two parents were randomly assigned to the intervention or treatment-as-usual group. Four parents assigned to the intervention group did not continue after baseline testing. Results: The intervention was delivered successfully with low drop out (10%), high session completion (97%), and high program adherence. The intervention conditions showed significantly greater gains over time for knowledge, confidence, perceptions, and monitoring related to hearing aid management. Significant differences between groups were not observed for hearing aid use time. Conclusion: We found that we could successfully implement this eHealth program and that it benefitted the participants in terms of knowledge and confidence with skills important for hearing aid management. Future research is needed to determine how to roll programs like this out on a larger scale.